2019
DOI: 10.33594/000000166
|View full text |Cite
|
Sign up to set email alerts
|

JAK2/STAT3 Pathway is Required for α7nAChR-Dependent Expression of POMC and AGRP Neuropeptides in Male Mice

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the past few years, our group has shown that α7nAchR activation in mice hypothalamus plays an important role in regulating the expression of anorexigenic neuropeptides, resulting in the reduction of food intake [ 14 ]. However, hypothalamic expression of α7nAchR can be impaired under pro-inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, our group has shown that α7nAchR activation in mice hypothalamus plays an important role in regulating the expression of anorexigenic neuropeptides, resulting in the reduction of food intake [ 14 ]. However, hypothalamic expression of α7nAchR can be impaired under pro-inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Stattic was given according to previous study (Souza et al, 2019). The cannula was connected with a polyethylene tube to a Hamilton syringe.…”
Section: Drug Administrationmentioning
confidence: 99%
“…Additionally, the association of α7 nAChR with Janus kinase 2 (JAK2) has been described, and this association leads to activation of the signal transducer and activator of transcription 3 (STAT3), resulting in a localization of STAT3 to the nucleus in neuronal mypHoA-POMC/GFP cells, where it then serves as transcription factor [ 101 ] ( Figure 1 ). However, α7 is not the only nAChR coupled to JAK2.…”
Section: Metabotropic Signaling Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%